STAT6-induced production of mucus and resistin-like molecules in lung Club cells does not protect against helminth or influenza A virus infection - Ruhl, Andreas; Vieira Antao, Ana Isabel; Dietschmann, Axel; Radtke, Daniel; Tenbusch, Matthias; Vöhringer, David (European Journal of Immunology, 2023)
Airway epithelial cells contribute to a variety of lung diseases including allergic asthma, where IL-4 and IL-13 promote activation of the transcription factor STAT6. This leads to goblet cell hyperplasia and the secretion of effector molecules by epithelial cells. However, the specific effect of activated STAT6 in lung epithelial cells is only partially understood. Here, we created a mouse strain to selectively investigate the role of constitutively active STAT6 in Club cells, a subpopulation of airway epithelial cells. CCSP-Cre_STAT6vt mice and bronchiolar organoids derived from these show an enhanced expression of the chitinase-like protein Chil4 (Ym2) and resistin-like molecules (Relm-α, -β, -γ). In addition, goblet cells of these mice spontaneously secrete mucus into the bronchi. However, the activated epithelium resulted neither in impaired lung function nor conferred a protective effect against the migrating helminth Nippostrongylus brasiliensis. Moreover, CCSP-Cre_STAT6vt mice showed similar allergic airway inflammation induced by live conidia of the fungus Aspergillus fumigatus and similar recovery after influenza A virus infection compared to control mice. Together these results highlight that STAT6 signaling in Club cells induces the secretion of Relm proteins and mucus without impairing lung function, but this is not sufficient to confer protection against helminth or viral infections.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Aspergillus fumigatus; Club cell; Influenza a virus; Mucus; Nippostrongylus brasilienis; Relm-α; STAT6